The Handmaid’s Tale as Palimpsest Biblical (Re)Imaginings in Margaret Atwood’s Novel - Jeffers, Ann (Journal for Religion, Film and Media)
The Handmaid’s Tale inhabits an imaginary space defined by biblical narratives at a time set in the near future when low fertility has reached a critical point. The solution provided by the Bible-based totalitarian regime in place in Gilead is to offer “handmaids” as surrogate mothers to members of the ruling elite. The biblical basis for this is chillingly re-enacted through the set reading of Genesis 30:1-3 preceding and legitimising the ritual rape of the household dedicated handmaiden. While this text clearly provides the rationale for addressing issues of fertility in Gilead, I will focus more specifically on how the book of Judges (specifically Judges 19-21) is marshalled to provide an implicit framework for The Handmaid ’s Tale. The paper will analyse the complex ways in which the Bible is used and abused in both the novel and the fourth series, using literary and feminist lenses. It will be argued that both narratives, the Book of Judges and Atwood’s tale contain elements of subversion and deconstruction.